2020
DOI: 10.2741/4839
|View full text |Cite
|
Sign up to set email alerts
|

The role of iron in viral infections

Abstract: Introduction 2.1. Human iron homeostasis 2.2. Iron and the immune system 2.3. Damaging effects of cellular iron 3. Iron in viral infections 3.1. Role of iron in HBV infection 3.2. Role of iron in HCV infection 3.3 Role of iron in HCMV infection 3.4. Role of iron in HIV infection 4. Conclusion 5. References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 23 publications
(3 reference statements)
1
46
0
1
Order By: Relevance
“…It has been shown that iron overload in human immunodeficiency virus (HIV), hepatitis B (HBV) and hepatitis C (HCV) is a risk factor for severe disease and increased mortality. Homozygous and heterozygous mutations in HFE C282Y have been shown to cause hepatic iron overload promoting steatosis and liver fibrosis in HCV-infected patients [1] . It has been further suggested that limiting iron availability to infected cells by using iron chelators could be a beneficial therapy in viral infections [2] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that iron overload in human immunodeficiency virus (HIV), hepatitis B (HBV) and hepatitis C (HCV) is a risk factor for severe disease and increased mortality. Homozygous and heterozygous mutations in HFE C282Y have been shown to cause hepatic iron overload promoting steatosis and liver fibrosis in HCV-infected patients [1] . It has been further suggested that limiting iron availability to infected cells by using iron chelators could be a beneficial therapy in viral infections [2] .…”
Section: Discussionmentioning
confidence: 99%
“…The key role of iron in viral infections is well described, although not fully understood. Iron is an essential factor for successful viral replication within living hosts and replete intracellular iron stores provide favourable conditions for this process 1 , 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the host's iron status can alter the course of infection and its resolution. Moreover, viral infections need active cell metabolism and, therefore, a significant viral replication requires a high iron availability [28,29]. As a matter of fact, iron homeostasis disorders including Fpn, TfR1 and Ftn dysregulated synthesis lead to an intracellular iron overload which facilitate viral multiplication and spreading.…”
Section: Iron and Inflammatory Homeostasismentioning
confidence: 99%
“…Viral infections need active cell metabolism and, therefore, a significant viral replication requires a high iron availability [82]. As a general rule, intracellular iron overload, induced by up-expression of hepcidin, promotes the progression of viral infections, as demonstrated for the human immunodeficiency virus (HIV) [83]. Conversely, HCV infections represent a peculiar exception, presenting the down-regulation of hepcidin, which is then up-regulated following antiviral therapy [81].…”
Section: Figurementioning
confidence: 99%